The effect of individual-level factors in survival prognosis for colorectal cancer in Malaysia - Ghazali, Anis K.; Keegan, Thomas J.; Abu Hassan, Mohd R.; Taylor, Benjamin M. (International Journal Of Community Medicine And Public Health, 2019)
Background: In Malaysia, colorectal cancer is the second most common type of cancer for both sexes, represents 10.2% of total cancer cases in Malaysia. This study aims to identify the effect of individual-level factors on survival prognosis for patients with colorectal cancer in Malaysia. Methods: The study involved 4412 of colorectal cancer patients in Malaysia with histologically verified primary colorectal cancer, diagnosed between 2008 and 2013 (ICD-10, C18-C20), recorded in the database of National Cancer Patient Registry- Colorectal Cancer (NCPR-CC) Malaysia. We investigated the effect of individual characteristics such as age, gender, education as well as clinical characteristics such as cancer staging, cancer site and treatment modalities on survival prognosis after a diagnosis of colorectal cancer using a Cox regression survival model. Results: Patients diagnosed at stage IV had an almost 6-fold greater risk of dying from colorectal cancer than those with stage I. Age, third-degree education, poor tumour differentiation, the presence of distant metastases and receiving ‘other’ treatments were the other factors that increased the risk of death for colorectal cancer patients in Malaysian population. Conclusions: Our analysis revealed that the severity of the disease lead to poor prognosis in colorectal cancer in the population after adjusting for other individual characteristics. Health education programs targeting high risk group and emphasizing the importance of early detection of cancer as well as knowledge on the importance of cancer treatment should be implemented. Formulation of a better screening program needs to be extended so that it is a genuinely national program.